Evidence-Based Alignment of Pathology Residency With Practice - W. Stephen Black-Schaffer MD; David J. Gross PhD; James M. Crawford MD, PhD; Stanley J. Robboy MD; Kristen Johnson PhD; Michael B. Cohen MD; Melissa Austin MD; Joseph Sanfrancesco MD; Donald S. Karcher MD; Suzanne Z. Powell MD; Rebecca L. Johnson MD (Elsevier, 2018)
Few medical specialties engage in ongoing, organized data collection to assess how graduate medical education in their disciplines align with practice. Pathology educators, the American Board of Pathology, and major pathology organizations undertook an evidence-based, empirical assessment of what all pathologists need to learn in categorical residency. Two challenges were known when we commenced and we encountered 2 others during the project; all were ultimately satisfactorily addressed. Initial challenges were (1) ensuring broad representation of the new-in-practice pathologist experience and (2) adjusting for the effect on this experience of subspecialty fellowship(s) occurring between residency and practice. Additional challenges were (3) needing to assess and quantify degree and extent of subspecialization in different practice settings and (4) measuring changing practice responsibilities with increasing time in practice. We instituted annual surveys of pathologists who are relatively new (<10 years) in practice and a survey of physician employers of new pathologists. The purpose of these surveys was to inform (1) the American Board of Pathology certification process, which needs to assess the most critical knowledge, judgment, and skills required by newly practicing pathologists, and (2) pathology graduate medical education training requirements, which need to be both efficient and effective in graduating competent practitioners. This article presents a survey methodology to evaluate alignment of graduate medical education training with the skills needed for new-in-practice physicians, illustrates an easily interpreted graphical format for assessing survey data, and provides high-level results showing consistency of findings between similar populations of respondents, and between new-in-practice physicians and physician-employers.